Cyber Physical Systems for Smart Cities Development - A.Jabbar, M.; Samreen, Shirina; Aluvalu, Rajanikanth; Kiran Reddy, K. (International Journal of Engineering and Technology, 2018)
With the technological advances in ICT people are migrating to urban areas. Urbanization becomes a global phenomenon. By 2030, 60% of the population will live in urban. Development of smart cities is inevitable. Cyber Physical Systems (CPS) supports our day to day activities. With the emergence of CPS is becoming more important to smart cities. Smart cities can be viewed as large scale implementations of CPS. This paper throws some light on the concepts of CPS, Smart and the various challenges posed by CPS in implementing in smart cities .This paper also describes research directions for CPS .Â Â